A new species of bamboo-feeding leafhopper genus Myittana from India (Hemiptera: Cicadellidae) - Ramaiah, Mogili; Meshram, Naresh M. (Zootaxa, 2021)
A new bamboo leafhopper species, Myittana (Myittana) bidentata sp. nov. is described and illustrated from India (Pantnagar, Uttarakhand). The new species is similar to Myittana (Myittana) distincta but can be distinguished by its large size (7.8 mm long) and the male genital structure. An annotated species checklist of the genus and key to species of the subgenus Myittana (Myittana) are also provided.